Construction and evaluation of a height prediction model for children with growth disorders treated with recombinant human growth hormone - Feng Zhu; Anle Wu; Lingling Chen; Ya Xia; Xiaoju Luo; Jieqian Zhu; Lina Huang; Yu Zhang (BMC Endocrine Disorders)
Abstract Background Height gain in children with growth disorders undergoing recombinant human growth hormone (rhGH) therapy shows considerable variability. Predicting treatment outcomes is essential for optimizing individualized treatment strategies. Objective To develop and evaluate a predictive model using clinical data to assess early height growth response in children with growth disorders undergoing rhGH therapy. Methods A total of 786 children were included, randomly split into a derivation cohort (N = 551) and a test cohort (N = 235). Multiple machine learning models were built in the derivation cohort, including logistic regression, decision tree, random forest, XGBoost, LightGBM, and multilayer perceptron (MLP). Model performance was evaluated in the test cohort using area under the receiver operating characteristic curve (AUROC), area under the precision-recall curve (AUPRC), and accuracy metrics. Input variables included chronological age, height standard deviation score (HSDS), body mass index standard deviation score (BSDS), IGF-1, and the difference between bone age and chronological age (BA-CA). Results The random forest and MLP models performed best. The random forest model achieved an AUROC of 0.9114 and an AUPRC of 0.8825. The MLP model showed accuracy, precision, specificity, and F1 scores of 0.8468, 0.8208, 0.8583, and 0.8246, respectively. Chronological age, BA-CA, HSDS, and BSDS were the most influential variables. The decision tree identified HSDS ≥ -0.72 as the primary split point. Conclusion Machine learning models, especially random forest and MLP, predict height gain effectively in children receiving rhGH therapy, aiding personalized treatment. Despite MLP’s strong performance, its “black-box” nature may limit clinical adoption. Future work should focus on enhancing model interpretability.